2021
DOI: 10.15507/2413-1407.116.029.202103.666-685
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rates in Russian Regions in the Context of the COVID-19 Pandemic

Abstract: Introduction. The COVID-19 (coronavirus) pandemic has had a strong impact on the socio-economic situation in the country, especially on demographic processes. The article analyzes the change in the mortality rates in Russian regions and assesses the influence of various factors on them during the pandemic. Materials and Methods. The paper examined data from the Federal State Statistics Service on mortality rates in Russian regions. Based on the graphs analyzed and regression equations built, the factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Another study on the structure of excess mortality in Russia in 2020 demonstrated a faster increase in mortality among urban residents compared to rural residents (Sabgaida 2021). Likewise, a study conducted by Druzhinin and Molchanova (2021) shows a significant positive relationship between increased mortality in the Russian regions in 2020 and the share of urban population.…”
Section: What Is Behind the Covid-19 Spread: Overview Of Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…Another study on the structure of excess mortality in Russia in 2020 demonstrated a faster increase in mortality among urban residents compared to rural residents (Sabgaida 2021). Likewise, a study conducted by Druzhinin and Molchanova (2021) shows a significant positive relationship between increased mortality in the Russian regions in 2020 and the share of urban population.…”
Section: What Is Behind the Covid-19 Spread: Overview Of Studiesmentioning
confidence: 94%
“…At the same time, both theoretical models of the infection transmission (Kalinin et al 2020) and empirical studies (Goroshko and Patsala 2021;Zemtsov and Baburin 2020) prove that morbidity and, therefore, mortality among the elderly is lower compared to young people, in particular, because older people have a more responsible attitude towards their health, have fewer social contacts (do not work, do not travel daily by public transport during rush hours) and voluntarily comply with all prohibitions and restrictions, sometimes even after they are officially cancelled. The study conducted by Druzhinin and Molchanova based on the 2020 data of the Russian regions, shows that the share of pensioners turned out to be an insignificant factor in assessing increase in mortality (Druzhinin and Molchanova 2021).…”
Section: What Is Behind the Covid-19 Spread: Overview Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…По наблюдениям многих авторов, снижение числа госпитализаций и ошибки маршрутизации больных могли оказаться следствием атипичной клинической картины ИМ у больных COVID-19. Все это также оказало влияние на увеличение внегоспитальной летальности от сердечно-сосудистых причин [9][10][11].…”
Section: результаты эпидемиология им в период пандемии Covid-19unclassified
“…A number of studies since the onset of the pandemic [3][4][5][8][9][10][11][12][13][14][15] described the impact of the pandemic using specific mortality indicators, such as infection fatality rate (IFR) and case fatality rate (CFR). These widely used measures of infection prevalence are sensitive to certain demographic and socioeconomic conditions, which may vary from country to country.…”
Section: Introductionmentioning
confidence: 99%